Analisis Legitimasi Diri dalam Budaya Organisasi Kepolisian: Studi Literatur - Supraptono, Supraptono; Muhdiarta, Untung (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2024)
This article aims to conceptually examine the sources of self-legitimacy from endogenous (internal to the organization) and exogenous (external to the police organization) factors. The novelty of this article is that the background characteristics of self-legitimacy have not been highlighted in previous studies. It would be a significant plus if future empirical research on police self-legitimation considered both endogenous and exogenous effects. Such scientific advances can help identify effective levers to achieve desired changes in policing. The methodology used in this research is qualitative, using a literature review approach. The steps used in qualitative data analysis include the stages of data reduction, data presentation, conclusion drawing or verification. The research shows that most police work is not focused on law enforcement, but consists of various social services of self-legitimization. The source of self-legitimation in this study shows that there is a link between police officers' self-legitimation and organizational culture.